The Need for Children's Advocacy Centres: Hearing the Voices of Children. Issue 4 (2nd October 2022) - Cook, Dianne L.; Livesley, Joan; Long, Tony; Sam, Mfon; Rowland, Andrew Graeme
ABSTRACT: Children and young people (CYP) can be empowered to take on roles as agents of change in their own communities. CYP want to be heard and should be actively involved in the co-production, design and development of services aimed at them to ensure that the resulting services are acceptable and accessible. Little analysis of the framing and discourse of co-production in different contexts has been undertaken. Building on Children's Advocacy Center models from the United States of America (which are held in high esteem by local communities), there is perceived value of such a center in the UK. A service development initiative was designed to work with children from Greater Manchester (UK) to determine the potential for the establishment of a children's advocacy center in the North of England. This report presents the design and outcome of the initiative and contributes to the literature on the co-production of such service development projects with CYP, notably the means of achieving that outcome. Recommendations are made for the piloting of an Advocacy House model in the UK with collaborative efforts between CYP as well as health, education, law enforcement, social care providers, charities and voluntary groups. A community-inclusive partnership, underpinned by the principles of co-production and co-design, is integral to the further development of this pilot.